D. João de Castro Bank, a shallow water hydrothermal-vent in the Azores: checklist of the marine molluscs. - Ávila, Sérgio P. (2008)
D. João de Castro Bank (DJC) is a shallow seamount with hydrothermal activity located between the islands of Terceira and São Miguel, Azores (Portugal). Due to its remote location, few investigators have worked in the area. Thirty-three species of marine molluscs are recorded as new for DJC which brings the total number of species to 42 for this specific area. Common micro-mollusc species known for the Azores (e.g.: the sublittoral species Alvania poucheti and Setia subvaricosa) are not present, and possible reasons for this are discussed.